CsPbBr 3 을 기반으로 한 Perovskite 선량계의 방사선치료 Quality Assurance에 대한 적용가능성 평가 - 양승우; Seung-woo Yang; 박성광; Sung-kwang Park (한국방사선학회 논문지, 2022)
방사선치료에서는 정상조직에 대한 피해를 최소화하면서도 종양조직을 죽이기 위하여 정확한 정도관리 품질보증이 요구된다. 이를 위해서 치료 방사선을 정확하게 계측할 수 있는 선량계가 요구된다. 본 연구에서는 기존 사용되는 검출기 재료로 사용되는 물질보다 저렴하고 제조 공정이 간단하여 기존 물질들을 대체할 수 있는 페로브스카이트 물질에 제조단가를 낮출 수 있고 공정을 간소화 시킬 수 있는 particle in binder(PIB) 방법을 적용하여 민감도가 높은 고효율의 방사선 선량계를 개발하고자 하였다. 고에너지 광자선에 대한 반응특성을 평가함으로써 방사선치료분야에 정도관리 품질보증선량계로 적용 가능한지 적용가능성을 평가하였다. 재현성 평가 결과, 6 MV 에너지에서의 RSD 1.178%로 제시되었고 15 MV에너지에서는 1.141%로 제시되었다. 선형회귀분석에 따른 선형성 평가결과, 6 MV, 15 MV 에너지 각 조건에서 0.9999의 R 2 값을 제시하였다. 재현성, 선형성 평가결과를 바탕으로 제작된 CsPbBr 3 선량계의 치료방사선 분야에 정도 관리 품질보증 선량계로의 적용가능성이 높은 것으로 나타났다. 본 연구에서 제작된 CsPbBr 3 선량계는 재현성, 선형성 평가에서 기준이상의 성능을 제시하였으며, 개선을 통하여 치료방사선 정도관리 품질보증 선량계로 활용 가능한 것으로 판단된다. In radiation therapy, accurate Quality Assurance (QA) is required to irradiate tumor tissue while minimizing damage to normal tissue. Therefore, a dosimeter that can accurately measure radiation is needed. The purpose of this study is to develop a highly efficient radiation dosimeter with high sensitivity by applying a particle in binder method that can reduce manufacturing costs and simplify processes to perovskite materials that are cheaper and simpler to manufacture. By evaluating the response characteristics to high-energy photon, the applicability of QA dosimeter to radiation therapy was evaluated. As a result of reproducibility evaluation, RSD at 6 MV energy was presented as 1.178% and 15 MV energy was presented as 1.141%. As a result of linearity evaluation according to linear regression analysis, R 2 values of 0.9999 were presented under each condition of 6 MV and 15 MV energy. It was found that the CsPbBr 3 dosimeter manufactured based on the results of reproducibility and linearity evaluation is highly applicable as a QA dosimeter in the field of therapeutic radiation. The CsPbBr 3 dosimeter manufactured in this study presented more than the standard performance in the evaluation of reproducibility and linearity, and it can be used as a radiotherapy QA dosimeter through improvement.